Untersuchungen über die Beziehungen der Eilänge zur Weibchen- und Gelegegröße bei Anopheles claviger typicus Meigen mit Hinweisen auf die Längenentwicklung der Larven (Untersuchungen über die Insektenfauna von Räumen Nr. 15) (Diptera: Culicidae). - Kühlhorn, Friedrich jun. (Contributions to Entomology = Beiträge zur Entomologie, 1967)
A study was made of the length of the eggs of Anopheles claviger Meigen in proportion to the size of the females and the number of eggs laid in one batch, and the development in size of the larvae was observed. - The examinations revealed no connections between the average length of the eggs and the size of the female or the number of eggs laid in one batch. - Nor could a general tendency in the relation between length of egg and length of egg larva be established. These results appear to confirm to a certain degree the widely held opinion that the growth of the larvae of this species (and thus the size of the imago) is mainly influenced by the environment conditions of the breeding habitat.